Environmental literacy of biology teacher candidates in supporting the Walisongo Eco Green Campus program - Ndzani Latifatur Rofi'ah; Noor Amalia Chusna (JPBI (Jurnal Pendidikan Biologi Indonesia), 2022)
Education is crucial in changing human behaviour toward environmental management. The Walisongo Eco-Green Campus (WeGreen) is a program that aims to achieve Sustainable Development Goals, so it is necessary to prepare the students of Biology teacher candidates to have good environmental literacy. This study aims to describe the environmental literacy of the students of Biology teacher candidates based on the academic year. The sampling technique used in this study was stratified random sampling. The sample of the study was 339 students of Biology teacher candidates in four different academic years. Data collection techniques used are tests and questionnaires. The data obtained from the measurement result of environmental literacy were analyzed descriptively using the mean and standard deviation formulas. The results of the Kruskal-Wallis test show a significance value of 0.451 (p>0.05) on the cognitive aspect and 0.535 (p>0.05) on the affective aspects. In addition, the result on behavioural aspects is 0.012 (p<0.05). There is no difference in environmental literacy (cognitive aspects and affective aspects) of the students of Biology teacher candidates based on the academic year, but there is a difference in students’ behaviour aspects. Students with the most different behaviour are those in the academic year of 2019 (fifth semester).